Impact of Anthropization on the Copper and Zinc Contents of Urban Soils. Case of the Concession of the Company Textile for Kisangani (SOTEXKI) in Kisangani in the Province of Tshopo in DR Congo - Kombele M; Ofeka L; Bola D; Kirongozi F; Ugencan D; Lifafu H; Kakuni J; Kombele F (Budapest International Research and Critics University, 2022)
This research has set itself the task of studying the impact of anthropization on the copper and zinc contents of urban soils in the concession of the Textile company of Kisangani (SOTEXKI) in Kisangani in the Province of Tshopo in the DR. Congo. To do this, the soil samples were taken from 6 soil slices: 0-10, 10-20, 20-30, 30-40, 40 -50 and 50-60 cm, thus giving a total of 18 spot samples per substation, i.e. a total of 126 grab samples with the reference station (dense forest). The 126 composite samples were reduced to 42 composite samples for all 7 substations using the auger. Conditioned, these samples were subjected to copper and zinc assays using an atomic absorption spectrophotometer using the ammonium acetate method at pH7 in the presence of EDTA. The results obtained show the following trends:- Soil copper content is higher is 387.95 µg/g and lower with 2.08 µg/g compared to all other land uses, the average soil zinc content is higher with 632 .98 µg/g and lower with 3.85 µg/g compared to all the other land uses of our neighboring station at the SOTEXKI/Kisangani plant. In general, the surface slices of the soils of different substations are richer in copper and zinc. Although generally higher than those of our reference (dense forest), the average values of the levels observed in our various substations are also higher compared to the global critical threshold (20-30 mg/kg of soil). - At this level of research, it is too early to certify that these levels are dangerous for human consumption of agricultural products from the soil of these substations. The impacts of anthropization are negative at the level of zinc, which means that the activities practiced in all the substations in our neighboring station to the factory of the textile company of Kisangani/Kisangani have drawn on the reserves of their soil in zinc more than copper, although in smaller quantities than for the latter.